BACK TO WORK POST-COVID-19 PANDEMIC: GENDER EQUALITY OF WOMEN WORKERS FROM THE POINT OF VIEW OF THE FIFTH SDGS - Utari, Dyah; Maharani, F. T. (UI Scholars Hub, 2022)
Staying at home and taking care of the family full time was the desire of most female workers in the pre-pandemic period. After the Covid-19 pandemic, working from home has become necessary, bringing its problems and negative impacts. The shift from the pandemic period to the new order era does not necessarily eliminate the double burden of working women. Economic conditions that have not yet recovered, difficulties in finding household assistants, anxiety about leaving children at home without knowledge are new problems that arise when female workers returning to work. This study looks at the double burden faced by female workers when they are required to return to work after the pandemic in comparison to male workers. The method used is a mixed method by combining quantitative and qualitative designs. The results showed that 39.18% of respondents were ready to work again. 55,60% have received socialization regarding the new rules in the workplace after the pandemic. From the Rapid Assessment Procedure results, it was found that women were more worried about the condition of leaving behind a child in comparison to men. Women workers also hope that the workplace can provide proper and safe childcare facilities. Inequality in caring for children after this pandemic can affect the realization of the five SDGs goals. The government is expected to be sensitive and make policies related to these conditions by providing facilities that can support the performance of women workers.